Re-exploitation of tapping panel dryness trees of Hevea brasiliensis - Xiaodi W; Chengxu W; Wanlin Y; Wenxian X (IRRDB Workshop on Tapping Panel Dryness in Hevea brasiliensis, Hainan, China, 1997; p55-62)
Resting trees affected by tapping panel dryness were treated and retapped for 3 successive years by employing vertical puncture tapping, upward tapping plus puncture tapping, and S/4 upward tapping after isolation of the infected patch and application of antibiotic compounds. Results showed that upward tapping plus puncture tapping of the treated trees gave a dry rubber yield of 1.546 kg/tree/year, 67;of that of the control (healthy trees), but the tapping frequency was only 30;of that of the control. Upward tapping plus puncture tapping gave more yield, consumed less bark and a less recurrent rate of TPD than conventional upward tapping or vetical puncture tapping. The tapping system is practical and easy to use.
Keywords: Hevea brasiliensis; TPD